Empowering tomorrow's changemakers: youth leadership in student representatives councils - Mohd Azhari Afirul; Calvina Angayung (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research paper explores the role of youth leadership in student representative councils (SRCs) and its impact on empowering young individuals as changemakers for nurturing a generation of responsible and compassionate leaders who can drive positive change, create stronger communities, and work towards a better future for all. The research addresses the following questions: How can SRCs serve as platforms for nurturing and developing youth leadership skills? How can youth leadership within SRCs drive positive change within educational institutions, and how does youth leadership development in SRCs benefit the individuals involved? The qualitative method involved face-to-face interviews with respondents who support the SRCs at the University Malaysia Sarawak (UNIMAS), focusing on student priorities. The selection of this informant is based on youth leadership in SRCs at UNIMAS. The data were analysed using thematic analysis by identifying and interpreting recurring themes or patterns in the qualitative data. The research observes and evaluates the key aspects of their leadership styles: communication, teamwork, problem-solving, and conflict-resolution skills. By shedding light on the effectiveness of youth leadership in SRCs, this paper seeks to inspire and encourage the development of future leaders committed to making positive changes in the development of students and the betterment of society at large.